Integrating GIS and the Global Positioning System - Steede-Terry, Karen (ESRI Press, 2000)
The coupling of the Global Positioning System (GPS) with Geographic Information System (GIS) is an information revolution that will give unprecedented accuracy in measurement and completeness of coverage to anyone who works with geographic data of any kind. This comprehensive reference answers the myriad questions involved in combining these two systems for maximum benefit. It provides information about how GPS works, the pros and cons of implementing GPS use, what is the best GPS system for specific applications, and how to integrate the technology and equipment needed to use GPS with existing GIS systems. Real-life case studies give users the opportunity to consider every aspect of systems integration before the process is started. Includes CD-ROM.